Benthic environmental impact of deep sea cage and traditional cage fish mariculture in Yellow Sea, China. (11th June 2021) - Zhao, Yunxia; Zhang, Jihong; Qu, Dapeng; Yang, Yanyun; Wu, Wenguang; Sun, Ke; Liu, Yi
Abstract: Using the Modelling‐Ongrowing fish farms‐Monitoring B investigation system (MOM‐B), we discussed the effects of deep sea cage (DSC) and traditional sea cage (TSC) fish mariculture on benthic environments in the Yellow Sea, China. Macrofauna, and chemical and sensory parameters were evaluated at 10 field stations surrounding a traditional sea cage farm in 2016–2017 and 10 field stations surrounding a deep sea cage farm in 2018–2019. Benthic macrofauna were found in all samples, and biological parameters were universally rated acceptable or better. In spring and winter, the pH and redox potential values near the DSC farm were within the score 0, while in summer and autumn, values were within the score 1. In TSC farm, most scores were in the score 0 in spring and autumn and in the score 1 in summer. Chemical parameter results showed the DSC and TSC farms were all in condition 1, whereas the sensory parameters near the DSC farm were in condition 1, and the TSC farm in condition 2. Finally, the results demonstrate benthic environments near the DSC farm were better than those near the TSC farm. MOM‐B system provides a practical environmental assessment tool that is simple, cheap and easy to implement and can be performed by moderately trained personnel.